Recovery of stolen cultural property after years of theft - Grajewski, Adam (Acta Universitatis Lodziensis. Folia Iuridica, 2018)
Nowadays, demand and will to possess works of art and monuments is rapidly increasing, but at the same time the quantity of them is not increasing to meet the demand. Theft of art does not cause decrease in its value, on the contrary, its long-term storage even increases the value. This situation results in an increase of its market value, which becomes the tempting object of the crime. Criminal groups have also recognized the situation and they well know needs of the collector’s market and take advantage of them. In the 90-ies there were many burglaries at sacra buildings, museums and private houses in which mainly works of art were stolen. Currently, we can observe that the pieces of art, which were lost in those years appear more and more often on the art. market.